2020
DOI: 10.1074/jbc.ra120.012635
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling and protease inhibition experiments identify proteases that activate H3N2 influenza A and influenza B viruses in murine airways

Abstract: Cleavage of influenza virus hemagglutinin (HA) by host proteases is essential for virus infectivity. HA of most influenza A and B (IAV/IBV) viruses is cleaved at a monobasic motif by trypsin-like proteases. Previous studies have reported that transmembrane serine protease 2 (TMPRSS2) is essential for activation of H7N9 and H1N1pdm IAV in mice, but that H3N2 IAV and IBV activation is independent of TMPRSS2 and carried out by as-yet-undetermined protease(s). Here, to identify additional H3 IAV- and IBV-activatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Whether these TTSPs play a role in viral spread in the host is incompletely understood. For IAV, infection by H3N2 viruses were found not to be fully TMPRSS2 dependent ( 38 , 42 ) and an auxiliary role of TMPRSS4 in spread and pathogenesis of H3N2 viruses has been reported ( 43 , 44 ). Moreover, influenza B viruses can use a broad range of TTSPs in cell culture ( 44 , 45 ) and a prominent role of TMPRSS2 in viral spread in type II pneumocytes has been reported ( 46 ) but viral spread in mice is TMPRSS2 independent ( 44 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these TTSPs play a role in viral spread in the host is incompletely understood. For IAV, infection by H3N2 viruses were found not to be fully TMPRSS2 dependent ( 38 , 42 ) and an auxiliary role of TMPRSS4 in spread and pathogenesis of H3N2 viruses has been reported ( 43 , 44 ). Moreover, influenza B viruses can use a broad range of TTSPs in cell culture ( 44 , 45 ) and a prominent role of TMPRSS2 in viral spread in type II pneumocytes has been reported ( 46 ) but viral spread in mice is TMPRSS2 independent ( 44 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…TMPRSS2 has a role in the entry of several coronaviruses, including SARS-CoV2, SARS-CoV, and MERS-CoV, as well as several types of influenza viruses (2,(8)(9)(10)(11)(12). TMPRSS2 also functions as an oncogene in prostate cancer, in which fusion events of TMPRSS2 and ERG2 occur (13).…”
Section: Discussionmentioning
confidence: 99%
“…viruses in a murine model (8). Notably, these viruses do not require TMPRSS2 priming, and the mechanism of A1AT function was suggested to be mediated by hepsin inhibition.…”
Section: Previously A1at Was Shown To Inhibit the Infection Of H3n2 mentioning
confidence: 99%
“…Based on the findings, we found that TMPRSS2 protein is a highly effective target for the treatment of COVID-19 caused by SARS-CoV-2 [29]. As TMPRSS2 plays an important function in the entry of SARS-CoV-2, MERS-CoV-2, and some influenza viruses into the host cell [5,6,8,10], targeting TMPRSS2 will become a more direct approach to control the infectious diseases caused by these viruses.…”
Section: Scoresmentioning
confidence: 94%
“…It has been reported that TMPRSS2 played an important role in the progression of SARS, Middle East respiratory syndrome (MERS), and some influenza infections in a similar manner as SARS-CoV-2. [2,[4][5][6][7][8][9][10]. The increased viral genomic mutations result in multiple physiognomies of protein structure, which represent a challenge to counter viral resistance to drugs.…”
Section: Introductionmentioning
confidence: 99%